Implementation Of Islamic Education Values Towards The Behavior Of The People Of Besilam Babussalam Padang Tualang Langkat Village (Analysis Of Syekh Abdul Wahab Rokan Tariqat) - Kurniawan, Indra; bahri, saiful; Liza, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The research objectives were to find out what the Islamic Educational Values are in the teachings of Tariqah Syekh Abdul Wahab Rokan, To find out the implementation process of Islamic educational values on the behavior of the people of Besilam Babussalam Village Padang Tualang Langkat and to find out the Impact of Community Behavior on the teachings of Tarekat Syekh Abdul Wahab Rokan. The research method used is descriptive qualitative. The source of the research data is the people of Besilam Babussalam Langkat Village. The results of the research found that the teachings of the Naqsbandiyyah Tariqat provide good results on people's behavior because these teachings contain Islamic educational values including: Knowledge of Monotheism, Fiqh, Sufism (Spiritual) Cultural, Social and Religious Heritage, so that the values of Islamic Education can be implemented by carrying out what has been ordered and leaving the prohibitions, in Tauhid (a strong community of belief in Allah), through Fiqh the community always practices the obligations that have been determined, in Sufism and Spirituality the community gets a clean heart which has an impact on good attitudes such as (Tawadhu, patience, sincere, wara' and asceticism). Maintaining or preserving the Tomb of Sheikh Abdul Wahab Rokan which is visited by many people from outside the region so that it can increase the ties of friendship among Muslims. Maintain good communication relations with visitors outside the area through the Haul. Still maintaining personality, a society that maintains practices in Islam